2020
DOI: 10.1177/0972150920937535
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic Shopping Motivations and Obsessive–Compulsive Buying on the Internet

Abstract: This article examines the relationship between online hedonic shopping motivations and obsessive–compulsive buying of online buyers. The useable data of 503 respondents are analysed through structural equation modelling (SEM). The results indicate that online buyers exhibit adventure seeking and idea shopping, which have a positive effect on obsessive–compulsive buying, whereas role shopping and value shopping are found to be negatively significant to obsessive–compulsive buying. Surprisingly, gratification se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 100 publications
2
31
0
Order By: Relevance
“…Therefore, H2 holds. This finding of this is consistent with the results from Ozturk et al [30] and Ozkara et al [70], Childers et al [22], To et al [26], Chiu et al [49], Wang [71] and Ali et al [72]. The hedonic value of online food delivery platforms is likewise valued by consumers, which shows that, although it is an online virtual platform, consumers still care about the overall shopping experience.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, H2 holds. This finding of this is consistent with the results from Ozturk et al [30] and Ozkara et al [70], Childers et al [22], To et al [26], Chiu et al [49], Wang [71] and Ali et al [72]. The hedonic value of online food delivery platforms is likewise valued by consumers, which shows that, although it is an online virtual platform, consumers still care about the overall shopping experience.…”
Section: Discussionsupporting
confidence: 89%
“…Wang [71] argued that hedonic values have higher positive associations with customers' intentions to buy than with the intent to search information. Ali et al [72] pointed out that hedonist value has an effect on consumers' purchase intentions. Wen-Kuo et al [73] pointed out that hedonic value is the main influence on impulse purchasing.…”
Section: Hedonic Valuementioning
confidence: 99%
“…The hedonic features of the online channel, have given rise to shopping which contributes to the development of obsessive–compulsive buying [ 47 ]. Consumers with compulsive tendencies have a constant preoccupation with shopping and use shopping as a means to reduce anxiety [ 48 ]. Research that has been carried out examines the relationship between hedonic shopping motivation and compulsive online purchases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More than just demographics, generation differences are also found to be important drivers towards buying. The shopping orientation of Gen Z is based on brand and quality (Ali et al, 2020), but during the pandemic, they were found to focus more on economic quality indicator and thereby becoming a convenience shopper. The demographic variables have been used as moderators in many studies to measure the impact of other factors on impulsive and panic buying.…”
Section: Demographics Burstsmentioning
confidence: 99%